SOCIOLOGY OF PRESCHOOL EDUCATION AND INTEGRATION OF EDUCATIONAL TASKS - Gulnara Narimanovna Eshchanova (Web of Journals Publishing, 2023)
In the article, the development of the education system and its impact on the development of society, the peculiarities of the education system in developed countries, in particular, pre-school education, are mentioned on the example of the USA. Sociology of preschool education system and educational tasks are analyzed in an integrated way. In the article, the issues of socialization and intellectual development of preschool children, integration and child care are analyzed in detail. The analysis is based on the comparative study of the works of a number of eminent scientists and the adopted laws and decisions on the system of preschool education in Uzbekistan.
Keywords: Integration, sociology, education, child, education, child disability, educational task, concept, intelligence, development.